1997
DOI: 10.1182/blood.v89.8.2706
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization, Molecular Cloning, and Expression of a Novel Hematopoietic Cell Antigen From CD34+ Human Bone Marrow Cells

Abstract: The adhesion molecule BEN/SC1/DM-GRASP (BEN) is a marker in the developing chicken nervous system that is also expressed on the surface of embryonic and adult hematopoietic cells such as immature thymocytes, myeloid progenitors, and erythroid progenitors. F84.1 and KG-CAM, two monoclonal antibodies to rat neuronal glycoproteins with similarity to BEN, cross-react with an antigen on rat hematopoietic progenitors, but F84.1 only also recognizes human blood cell progenitors. We have defined the antigen recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…ALCAM is known to be expressed on primitive human HSCs [29,30], however, its functional contribution to HSC biology has been unclear. This study provides a comprehensive characterization of the role of Alcam in regulating adult HSC function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALCAM is known to be expressed on primitive human HSCs [29,30], however, its functional contribution to HSC biology has been unclear. This study provides a comprehensive characterization of the role of Alcam in regulating adult HSC function.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ALCAM has been reported to mark a tumor-initiating cell population in prostate cancer and in lung cancer [27,28]. In the hematopoietic system, ALCAM is expressed on activated lymphocytes and monocytes and on primitive human HSCs [29,30]. In addition, Alcam is reportedly required for myeloid colony formation in avian embryonic hematopoietic progenitors [31], and Alcam-expressing endothelial cells can support murine embryonic hematopoiesis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Among adhesion molecules, the hyaluronate receptor CD44 was located on all basal cell membranes (Fig. 1E), and CD166, expressed otherwise by embryonic neuroblasts and by hematopoietic stem cells and stromal cells [30][31][32], was found on the apical and baso-lateral membranes of ciliated and secretory cells ( Fig. 1F).…”
Section: Antigenic Discrimination Of Epithelial Cell Subsets In Humanmentioning
confidence: 99%
“…Activated leukocyte cell adhesion molecule (ALCAM; CD166), also known as KG-CAM, neurolin, and BEN/DM-GRASP/SC1, is a novel member of the Ig superfamily, which is involved in homophilic adhesion and in binding to CD6 [12,13]. It is expressed on activated leukocytes [14], monocytes [15], hematopoietic progenitor cells [16], bone marrow stromal cells [17], and hematopoiesis-supporting osteoblastic cells [18]. ALCAM-mediated interactions are important during neural development [19], maturation of hematopoietic stem cells in blood-forming tissues [16,17,20], immune responses [21], and tumor progression [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed on activated leukocytes [14], monocytes [15], hematopoietic progenitor cells [16], bone marrow stromal cells [17], and hematopoiesis-supporting osteoblastic cells [18]. ALCAM-mediated interactions are important during neural development [19], maturation of hematopoietic stem cells in blood-forming tissues [16,17,20], immune responses [21], and tumor progression [22]. Although ALCAM was shown to mediate homotypic and heterotypic cell-cell clustering through homophilic (ALCAM-ALCAM) and heterophilic (ALCAM-CD6) interaction [14], Hassan et al [23] demonstrated recently that homophilic interaction was approximately 100 times weaker than heterophilic interaction.…”
Section: Introductionmentioning
confidence: 99%